A study of psychosocial burden of multi-transfused thalassemia children in a tertiary care hospital in North Bengal - Chowdhury, Sayantan; Gupta, Nikhil; Dutta, Abhijit; Nandi, Madhumita (International Journal of Contemporary Pediatrics, 2025)
Introduction: Thalassemia is an inherited disease of defective synthesis of hemoglobin. The name is derived from the Greek word "Thalassa" meaning "the sea". Thalassemia consists of a group of disorders that may range from a barely detectable abnormality of blood, to severe or fatal anemia. Adult hemoglobin is composed of two alpha (α) and two beta (β) polypeptide chains. The aim of the study was to evaluate the co-morbid psychiatric disorders of children with thalassemia who require regular blood transfusions. Method: The present study was an observational, descriptive study. This Study was conducted from February 2020 to July 2021 at department of Paediatric Medicine, North Bengal Medical College and Hospital, Darjeeling West Bengal. Total 60 patients were included in this study. Result: The distribution of CBCL internalization problem scores among the children were 28.3% above 63 and 21.7% in between 60-63; whereas, 50% of the children were having score of less than 60. The Distribution of CBCL externalization problem scores among the children were 23.3% above 63 and 20% in between 60-63; whereas, 56.9% of the children were having score of less than 60. Conclusion: In conclusion, this study highlights the significant psychosocial burden faced by children with thalassemia who undergo multiple blood transfusions. The findings underscore the profound impact on their mental health, social well-being, and quality of life, with these children often experiencing feelings of anxiety, depression, and social isolation.